Assessing the options for combatting democratic myopia and safeguarding long-term interests. (January 2021) - Boston, Jonathan
Highlights: The nature and causes of the presentist bias in democratic policy-making. The wide range of constitutional, institutional, policy-oriented and analytical proposals to counter the presentist bias. An assessment of the intervention logics underpinning proposals to counter the presentist bias. Strategies to safeguard long-term interests. Abstract: Faced with intertemporal policy conflicts, democratic political systems tend to favour short-term interests over long-term interests. Such phenomena, variously described as political short-termism, democratic myopia and a presentist bias in policy-making, threaten the interests of future generations. Numerous proposals – constitutional, institutional, policy-oriented and analytical – have been advanced to counter short-termism and protect long-term interests. While differing significantly, such proposals all rest for their claimed effectiveness on at least one of six theories of change or intervention logics: 1) changing the values and goals of policy-makers so that they care more about future interests; 2) changing the political incentives facing policy-makers such that it is in their interests to give more weight to long-term considerations; 3) enhancing the capacity of policy-makers to exercise foresight, thereby improving their anticipatory governance; 4) constraining the formal decision-rights of policy-makers when long-term interests are at risk; 5) insulating policy-makers from short-term political pressures; and 6) enhancing the capacity for coordination across different tiers of government and/or policy domains. Drawing upon and scrutinizing these six intervention logics, this paper assesses the feasibility, effectiveness and overall desirability of a selection of the proposals for combatting short-termism. Based on this analysis, a reform agenda is proposed.